2002
DOI: 10.1152/ajpendo.00444.2001
|View full text |Cite
|
Sign up to set email alerts
|

Shedding of TNF-α receptors, blood pressure, and insulin sensitivity in type 2 diabetes mellitus

Abstract: Tumor necrosis factor-α (TNF-α) is increasingly recognized as a key component in the development of insulin resistance and increased blood pressure. In a sample of 368 individuals, the ratio of soluble TNF-α receptors (sTNFR2/sTNFR1) correlated positively with systolic and diastolic blood pressure ( P < 0.01). This ratio was significantly greater in type 2 diabetic subjects (DM-2) than in type 1 diabetic patients and was greater than in control nondiabetic subjects ( P < 0.00001). The TNF-α receptor 1 (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
1
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 35 publications
(36 reference statements)
4
38
1
2
Order By: Relevance
“…7 TNF-a appears to be the critical cytokine in the process of endothelial stunning, 37 and has been associated to the insulin-resistant syndrome 16,40 and to HBP. 34,45 However, prospective cohort studies are needed to elucidate whether cytokine elevation predicts the development or is just a consequence of HBP. Knowledge of the contribution of CMI to HBP development could facilitate current efforts on detection, evaluation, and treatment of hypertension.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 TNF-a appears to be the critical cytokine in the process of endothelial stunning, 37 and has been associated to the insulin-resistant syndrome 16,40 and to HBP. 34,45 However, prospective cohort studies are needed to elucidate whether cytokine elevation predicts the development or is just a consequence of HBP. Knowledge of the contribution of CMI to HBP development could facilitate current efforts on detection, evaluation, and treatment of hypertension.…”
Section: Resultsmentioning
confidence: 99%
“…27,29 However, these studies have failed to control for other risk factors for HBP. On the other hand, Fernández-Real et al 45 have shown that the ratio of soluble TNF-a receptor 1 and soluble TNF-a receptor 2 (sTNFR1/ sTNFR2), a correlate of the degree of activation of the TNF-a system, is positively and significantly associated with systolic and diastolic blood pressure, and that lowering blood pressure decreases the sTNFR1/sTNFR2 ratio. Prolonged periods of low-grade systemic inflammation may explain the higher risk of HBP observed among subjects with obesity.…”
Section: Epidemiologic Evidencementioning
confidence: 99%
“…However, in experimental studies the degree of activation of the TNF-a system has been positively and significantly associated with systolic and diastolic BP. 33 Besides, TNF-a decreases endothelial nitric oxide synthase mRNA level by shortening its half-life. 34 This may result in decreased bioavailability of nitric oxide and lead to endothelial dysfunction, chronic vasoconstriction, and elevated BP.…”
Section: Discussionmentioning
confidence: 99%
“…Both genes encode peptides that can be produced by adipose tissue, and that can influence adipogenesis and lipogenesis in an autocrine/paracrine manner; in addition, when released into the circulation, they may regulate BP. 25,[27][28][29] As such, either of the 2 genes may exert pleiotropic effects on adiposity and BP. Alternatively, the locus may include 2 closely linked genes that cosegregate within families, with one being involved in the regulation of adiposity and the other in the control of BP.…”
Section: Discussionmentioning
confidence: 99%